Features of acoustic modeling as the final stage of acoustic examination of premises of audito-riums exemplified by a drama theater for 500 seats - Usik, V.; Myagkiy, I. (Radiotekhnika, 2017)
The final stage of the acoustic examination of the auditorium is considered on the example of the dramatic theater hall. Based on the results obtained in the first two stages, recommendations are developed on the use of finishing materials for the enclosing surfaces of the hall. The modeling of acoustic properties of the hall in the software package Ease 4.4 is carried out, the received objective characteristics of acoustic quality of the hall are analyzed.